Dampak Bimbingan Karier Pendekatan Holland terhadap Peminatan Sekolah Lanjutan Siswa Kelas X SMAN 3 Jember - Uma, Hanum Zakiyyatul; Budiono, Arifin Nur (FKIP Universitas Islam Jember, 2022)
The background of the research on the results of the questionnaire was that 51% of students already had a picture of their specialization in high school, 29% still had no picture, and 20% wanted to work. This study used a true experimental quantitative method through a pretest-posttest control group design. The sample selection was Stratified Random Sampling, and the result was that there were 2 homogeneous classes, then they are selected again using report cards to determine which students will become the control class and the experimental class. The control class that is not given career guidance with the Holland approach is in the category of no change in the Posttest questionnaire and the experimental class that is given career guidance with the Holland approach is in the category of changes in the Posttest questionnaire. This can be seen also from the results of data analysis using the t-test formula which states that the calculation results are in the rejection area of ​​Ho. This proves that there is impact of John Holland's career guidance on further study interests.